PENGARUH OPERATING CAPACITY, ARUS KAS OPERASI DAN BIAYA VARIABEL TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR TEXTIL DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2009-2016 - Dean Subhan Saleh (Eqien - Jurnal Ekonomi dan Bisnis, 2018)
This research aims to determine the influences of operating capacity, operating cash flow and variable cost to the possibility of companies experiencing financial distress. Currently, we can see the textile and garment industries, were all having profit descreased year by year. If its left constantly and continously, then the company will be at risk of facing financial distress condition. Financial distress is a condition that describes the downturn of corporate performance, so that they are having financial trouble full filling their short term liabilities. Population of this research are manufactured companies on textile and garment’s sectors listed on the Indonesian’s Stock Exchange 2009-2016 periods. By sampling defined with purposive sampling’s methods, there are 10 companies, selected as the research’s samples. And this research using regretions logistics analysis method on SPSS version 23. This research finally conclude that operating capacity significantly by positive having affects to the possibility of companies to suffer financial distress. Operating cash flow significantly by negative having affect to the possibility of companies to suffer financial distress and variable cost significantly by positive having affect to the possibility of companies to suffer financial distress. Keywords : operating capacity, operating cash flow, variable cost, financial distress.